The graph of g(x)=cot(x) is shown below.

We know that sin(-x)=-sin(x) and cos(-x)=cos(x).

So, `cot(-x)=\frac{cos(-x)}{sin(-x)}=\frac{cos(x)}{-sin(x)}=-cot(x)`

Hence, cot (x) is an odd function, and its graph is symmetric with respect to the origin.

## See

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

The graph of g(x)=cot(x) is shown below.

We know that sin(-x)=-sin(x) and cos(-x)=cos(x).

So, `cot(-x)=\frac{cos(-x)}{sin(-x)}=\frac{cos(x)}{-sin(x)}=-cot(x)`

Hence, cot (x) is an odd function, and its graph is symmetric with respect to the origin.